Produk Pengembangan Bahan Ajar Pai Dengan Pendekatan Interdisipliner - Miftakhul Azizah; Muhammad Arif; Burhanuddin AK. Mantau; Mujahid Damopoli (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the development of Islamic Religious Education teaching material products using an interdisciplinary approach through a literature review method. The review was conducted by analyzing various literatures, journals, and previous research related to teaching material development, interdisciplinary approaches, and Islamic Religious Education learning. The results of the review show that the interdisciplinary approach in developing Islamic Religious Education teaching materials can broaden students' perspectives, connect Islamic values with various fields of knowledge, and enhance the relevance of the material to real-life contexts. These findings emphasize the importance of teaching material innovation that not only focuses on the cognitive aspects of religion but also integrates social, cultural, scientific, and technological aspects. This study recommends that the development of interdisciplinary-based Islamic Religious Education teaching materials continue to be encouraged to support more contextual and holistic learning.